Bioaccumulation for some heavy metals in organs of Lethrinus nebulosus and concentrations in water and sediment Iraqi marine water - Al-Najar, Ghassan Adnan; Al-Faiz, Nawras A.; Al-Noor, Jalal M. (Iraqi Journal of Aquaculture, 2021)
The concentrations of heavy metals (iron, copper, nickel, lead and cobalt) were studied in many organs (muscle, liver, gonads and gills) of Lethrinus nebulosus fish hunted from the Iraqi marine waters, as well as, the water and sediments of the area. Metals concentration were measured by Flame atomic Absorption Spectrophotometer. The results showed that the highest values were recorded for iron 286.65 μg /g (dry weight) and the least concentration was for lead 1.74 μg /g (dry weight), nickel , copper and cobalt recorded (6.29, 9.89 and 19.71) μg /g (dry weight) respectively. Results showed that fish body parts that accumulated the metals were as follows: gills, liver, gonads and muscle, whereas the sequence of metals in fish body was as follows: iron, cobalt, copper, nickel and lead, whereas the sequence of metals according to season were: summer, spring, winter, autumn, winter. The results showed that the highest heavy metals concentrations of the sediment in winter was1250.98 65 μg /g (dry weight), while the lowest concentrations of heavy metals in water, was for lead and nickel 0.43 and 0.18 μg /L respectively, and in iron, cobalt and copper 4.11, 3.93 and 3.38 μg /L respectively.